EXAMINING THE ROLE OF ZAKAT AWARNESS ON THE INFLUENCE OF ZAKAT LITERACY, INCOME LEVELS, AND SOCIAL PIETY TOWARD MUZAKI'S DIGITAL PAYMENT - Jamaludin, Nur; Fauziah, Fauziah; Reslawati, Reslawati; Putri, Meisy Kurnia; Rosidi, Achmad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research aims to investigate the various effects of zakat literacy, income, and social piety on the decision-making process of Muzaki while choosing digital payment as a means to satisfy their zakat responsibilities at Rumah Yatim Karawaci. The study focuses exclusively on a purposive sample technique, with a stated aim of identifying persons who are registered as Muzaki at Rumah Yatim Karawaci. This research utilizes a descriptive quantitative method and employs Partial Least Square (PLS) analysis using Smart PLS Version 3.0 as the analytical technique. The research utilized a structured questionnaire as the data gathering technique. The empirical findings demonstrate that having knowledge and understanding of zakat (zakat literacy) has a significant and favorable impact on the decision-making process of Muzaki (those who pay zakat) when choosing digital payment as the method for distributing zakat funds. The conclusion is supported by a T statistic value of 2.074 and a corresponding P value of 0.039. In contrast, the factors of income and social piety are not statistically significant in relation to Muzaki's decision-making. In addition, the study found that social piety strongly influences zakat awareness, as indicated by a T statistic of 4.814 and a P value of 0.000. However, there is no statistically significant evidence to suggest that zakat literacy and income have an impact on zakat awareness. Moreover, the results of the Specific Indirect Effects analysis suggest that awareness does not act as a mediator between zakat literacy and income. The implication of this finding are that the zakat collecting institutions should enforce the awareness’ of muzakkis by socializing the important of distributing zakat to the zakat collecting agencies and also spreading the dakwah to enhance the social piety of the muzakkis.